Nowhere burning - Ward, Catriona (Nightfire/Tor Publishing Group, 2026)
"Riley and her brother Oliver set off in the pitch-black night, fleeing their troubled home. They are heading for Nowhere--an abandoned ranch, once the playground of its former eccentric movie-star owner, now a haven for runaways. What awaits could be the freedom they crave. But this mysterious clan guards dark secrets, and the scorched grounds hold the ghosts of the past. Riley quickly realizes that while she and Oliver may have escaped the devil they knew, something darker lurks in the burnt shell of Nowhere. Something which asks a terrible price for sanctuary..."--Provided by publisher.